Siam's New Detectives : Visualizing Crime and Conspiracy in Modern Thailand - Lim, Samson W., 1972- (Book collections on Project MUSE., 2016)
Visual evidence is the sine qua non of the modern criminal process - from photographs and video to fingerprints and maps. 'Siam's New Detectives', covering the period between the late 19th century and the end of the Cold War, offers an analytical history of these visual tools as employed by the Thai police when investigating crime.